FILSAFAT SEBAGAI CARA HIDUP - Fidelis Regi Waton (Jurnal Ledalero, 2019)
Abstract: Philosophy is often popularly accepted as an abstractscience and unrealistic. The reality of human life is not touchedby philosophy. This assumption must be falsified. Philosophy isnot a science that comes from another planet. From the beginning,philosophy was closely related to human reflection about his life inthe context of the macrocosm and microcosm. Philosophy thinksabout human life and presents a path to the goals of life bothpersonally and collectively. In this sense philosophy is not an purelyacademic matter, it is also not a private matter of philosophers, butit is an general matter. Everyone is able to philosophize.Keywords: Philosophy, way of life, wonder, wisdom, selfknowledge,enlightenment